PENGARUH WORKLIFE BALANCE DAN REWARD TERHADAP KINERJA KARYAWAN PADA PT. SUMATERA JAYA AGRO LESTARI (PT. SJAL) SEI LESUNG ESTATE - Alfian, Alfian; Ningsih, Erlina Rahayu (Ensiklopedia of Journal, 2024)
The purpose of this research is to examine the influence of work-life balance and reward variables on employee performance at PT. Sumatra Jaya Agro Lestari (Pt. Sjal) Sei Lesung Estate. This type of research is quantitative research. Quantitative research is research that can be explained using numbers and can be calculated using certain formulas and is based on percentage calculations and other statistical calculations. Data were collected through distributing questionnaires to 35 respondents using saturated sampling techniques, where all members of the population were sampled, the data sources in this research were primary data and secondary data, using instrument tests (validity test and reliability test), classical assumption tests ( normality test, multicollinearity test and heteroscedasticity test), multiple linear regression and hypothesis testing (t test) with the help of the SPSS application. The results of the research show that work-life balance has a positive and significant effect on employee performance, and rewards have a positive and significant effect on employee performance.